Discovery of Natural Products With Antifungal Potential Through Combinatorial Synergy - Augostine, Catheryn R.; Avery, Simon V. (Frontiers in Microbiology, 2022)
The growing prevalence of antifungal drug resistance coupled with slow development of new, acceptable drugs and fungicides has raised interest in natural products (NPs) for their therapeutic potential and level of acceptability. However, a number of well-studied NPs are considered promiscuous molecules. In this study, the advantages of drug-drug synergy were exploited for discovery of pairwise NP combinations with potentiated antifungal activity and, potentially, increased target specificity. A rational approach informed by previously known mechanisms of action of selected NPs did not yield novel antifungal synergies. In contrast, a high-throughput screening approach with yeast revealed 34 potential synergies from 800 combinations of a diverse NP library with four selected NPs of interest (eugenol, EUG; beta-escin, ESC; curcumin, CUR; berberine hydrochloride, BER). Dedicated assays validated the most promising synergies, including between EUG + BER, CUR + sclareol and BER + pterostilbene (PTE) [fractional inhibitory concentrations (FIC) indices < 0.5 in all cases], where minimum inhibitory concentrations were reduced to 35 mg L-1 (BER) and 7.9 mg L-1 (PTE). These three combinations synergistically inhibited a range of fungi, including human or crop pathogens Candida albicans, Aspergillus fumigatus, Zymoseptoria tritici and Botrytis cinerea. Further investigation indicated roles for mitochondrial membrane depolarization and ROS formation in the synergistic mechanism of EUG + BER action. This study establishes proof-of-principle for utilising high-throughput screening of pairwise NP interactions as a tool to find novel antifungal synergies. Such NP synergies, with potential also for improved specificity, may help in the management of fungal pathogens.